Peak factors of non‐Gaussian wind forces on a complex‐shaped tall building. (16th January 2012) - Huang, Mingfeng; Lou, Wenjuan; Chan, Chun‐Man; Bao, Sheng
SUMMARY: This paper focuses on the development of peak factor formulas of non‐Gaussian wind pressure processes after reviewing the current estimation methods of non‐Gaussian peak factors. A skewness‐dependent peak factor is proposed by accounting for the contribution of skewness and kurtosis parameters in some existing Hermite moment‐based formulas. The possible correction on the upcrossing rate used in the translation process approach is also investigated. Wind tunnel pressure data on a practical 43‐story building with unusual shape is used to validate the accuracy of the skewness‐dependent peak factor by investigating various statistical properties of wind‐induced fluctuating pressure field on the complex‐shaped tall building example. Copyright © 2012 John Wiley & Sons, Ltd.